(untitled) (Raparin Journal of Humanities (RJH), 2024)
The current study aims to determine the prevalence of social phobia among teenagers attending high schools in the Erbil city and its relationship to parental treatment strategies. It also compares the degree to which these teenagers experience social phobia based on their gender، their class at school، and whether they attend a public or private school. The researchers prepared a scale for measuring social phobia to identify the parental method’s treatment with their own teenager children after reviewing the literature and earlier studies related to the study’s topic. Following virtual validation of both scales’ validity and reliability using the Cronbach’s alpha method، the two scales were used to gather the necessary data from 402 students. The data collected was then analyzed using SPSS software to determine any significant relationships between parental treatment methods and their children’s phobias. The findings revealed that both male and female students have very low levels of social phobia. Parents are treating their adolescent children democratically rather than authoritarian، lenient، and neglectful. Furthermore، there are no statistically significant differences between male and female students based on sex، educational level، or school type (public or private). This suggests that adolescent with phobia may have experienced a range of parenting styles in their upbringing، but none of these styles were strong predictors of the development of phobia. The researchers concluded by offering a variety of advice and recommendations regarding social phobia in adolescents and its connection to parental treatment strategies. They concluded that more research is required to determine the long-term effects of different parental interventions on adolescents with social phobia